2011
DOI: 10.1186/1756-0500-4-298
|View full text |Cite
|
Sign up to set email alerts
|

Serum testosterone levels of HbSS (sickle cell disease) male subjects in Lagos, Nigeria

Abstract: BackgroundInfertility is a major problem in sickle cell disease patients, especially in males. In addition to low serum testosterone, other abnormalities involving the accessory sex organs, such as the seminal vesicles and the prostate gland, as well as marked decrease in ejaculate volume may be observed in male HbSS patients. Hence, the need to study the role of sex hormones as a cause of infertility in male HbSS patients.MethodsAn unmatched case-control study was performed using seventy-five consenting subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Several clinical studies have demonstrated decreased serum testosterone levels in male patients with SCD [ 6 – 12 ], with rates of testosterone deficiency as high as 25% [ 13 ]. Testosterone deficiency in SCD is associated with retardation of physical development [ 12 ], infertility [ 14 ], bone mass loss [ 7 ], and possibly priapism [ 13 ]. The mechanism underlying testosterone deficiency in SCD is not clear, as both increased and decreased luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels have been measured in SCD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have demonstrated decreased serum testosterone levels in male patients with SCD [ 6 – 12 ], with rates of testosterone deficiency as high as 25% [ 13 ]. Testosterone deficiency in SCD is associated with retardation of physical development [ 12 ], infertility [ 14 ], bone mass loss [ 7 ], and possibly priapism [ 13 ]. The mechanism underlying testosterone deficiency in SCD is not clear, as both increased and decreased luteinizing hormone (LH) and follicle-stimulating hormone (FSH) levels have been measured in SCD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility is a major problem in male sickle cell disease patients reported by Abudu et al in which they noted a lower testosterone levels in males compared with age-matched controls [16]. Impotence has also been reported in about a quarter of sickle cell disease patients secondary to priapism [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to low serum T, other abnormalities involving the accessory sex organs, such as the seminal vesicles and the prostate gland, as well as marked decrease in ejaculate volume and sperm parameters may be observed in male patients. [ 3 4 5 6 7 8 9 10 11 12 13 14 15 26 ] Recently, some data showed that blood transfusion produce significant acute changes in the hormonal milieu and sperm parameters of patients with chronic hemolytic anemia. [ 27 28 29 ] Therefore, we studied the acute effects of PCTx on spontaneous spermatogenesis and pituitary testicular axis in young eugonadal males with transfusion-requiring SCD (10 were on TTx and eight were on ETx).…”
Section: Discussionmentioning
confidence: 99%